Ekonomi Buruh Industri Pada Masa Pandemi Covid-19 - Ega Dini nur Rochma; Isa Anshori (EKONOMI & SOSIAL, 2021)
The coronavirus disease (Covid-19) pandemic that has infected many countries including Indonesia has had an impact on various sectors, especially the industrial sector, many companies have suffered losses and even closed their businesses, and this has also affected the labor economy. Likewise with PT. MASPION II is a giant company engaged in providing goods that has thousands of employees and factory workers, so this paper aims to provide an overview of the economic conditions of workers during this pandemic. The method used is a descriptive qualitative approach. This article examines the economic decline experienced by industrial workers at PT. MASPION II during the Covid-19 pandemic the results showed that there was a decrease in production caused by a decrease in the number of orders and the process of importing materials with a smaller frequency than the period before the pandemic. This decrease in production has an impact on reducing the working hours of workers which then affects the amount of wages they get, this condition is very hard on the family economy, but it is fully realized that this condition must be handled wisely, saving steps and having other sources of income are taken in the hope of being able to cover basic needs or needs. household routine.